2018
DOI: 10.1089/acu.2018.1291
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture as Adjuvant Therapy for the Management of Cervical Dystonia

Abstract: There are no curative treatments for cervical dystonia (CD), therefore conventional management is aimed at pain relief and muscle relaxation. Many patients with CD use complementary and integrative medicine interventions to manage symptoms, yet there are limited data on the use of acupuncture for CD. The aim of the current study was to determine the feasibility, safety, and efficacy of adjuvant acupuncture. A pilot open-label study was conducted on acupuncture treatments as add-on therapy to botulinum-toxin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…It is recognised that a range of non-specific interventions, such as hypnosis and acupuncture, can produce improvement or resolution of the symptoms and signs in focal dystonia including IB [12,13]. This improvement is usually inconsistent and unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that a range of non-specific interventions, such as hypnosis and acupuncture, can produce improvement or resolution of the symptoms and signs in focal dystonia including IB [12,13]. This improvement is usually inconsistent and unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…However, when considered holistically, it acts on multiple targets in the body, which might elicit corresponding feedback and adjustment relative to the local spasm, and the long-term effect might inhibit the spasm[ 70 ]. Studies have shown that acupuncture could serve as an adjuvant therapy, helping ST patients reduce the frequency of botulinum toxin usage and alleviate muscle tension[ 71 , 72 ]. Multiple studies suggest that acupuncture therapy can relieve muscle spasm in ST patients, and as it has no side effects, it provides a new treatment option for ST treatment[ 73 - 76 ].…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Currently, international guidelines recommend botulin as the first line treatment choice for CD, but long-term maintenance treatment may be required, leading to drug resistance or a series of side effects[ 6 ]. However, acupuncture is also effective in the treatment of CD[ 7 ]. In the treatment of CD, acupuncture should be used as needed to help improve the clinical outcomes[ 8 ].…”
Section: Introductionmentioning
confidence: 99%